Financial Feasibility Analysis of Purwogrape Grape Business in Tegaldlimo District, Banyuwangi Regency - Minuk Sri Haryati (CV Projurnal Mitra Publikasi, 2025)
Tegaldlimo District in Banyuwangi Regency has the potential for grape cultivation. One of the businesses engaged in grape production in this district is Purwogrape. The increasing market demand for grapes, both domestically and internationally, presents a significant opportunity to enhance farmers' incomes. However, a comprehensive financial feasibility analysis is essential to ensure the long-term sustainability of the business. This study aims to evaluate the financial viability of the Purwogrape grape business. The research employs cash flow analysis and investment feasibility assessment. The results indicate that the Purwogrape grape business in Tegaldlimo District is financially viable. The Net Present Value (NPV) is Rp1,056,296,819, while the Internal Rate of Return (IRR) is 40%. The payback period is calculated to be 2.38 years, or approximately 2 years and 4 months. The Benefit-Cost (B/C) ratio is 5.1, which is greater than 0. Additionally, the Revenue-Cost (R/C) ratio is 2.0 (R/C > 1.3), and the Gross B/C ratio is 1.8 (Gross B/C > 1), further confirming the business's profitability.